On Some Results of a New Fractional Calculus in the Unit Disk and its Applications - Atshan, Waggas Galib; Ali, Hisham Mohammed; Hamid, Duaa Mohammed (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
In this paper, we study a new definition of fractional calculus (fractional derivative-(Î²,Ï’),fractional integral-(Î²,Ï’),by depending of Srivastava-Owa fractional operators,and study some properties and provided of operators-(Î²,Ï’)and Applecations by using fractional complex transform for fractionaldifferential equations , Distortion inequalities and establishing the sufficient conditions for the existence and uniqueness of Cauchy problem in the unit disk.